Multipulse nanosecond laser irradiation of silicon for the investigation of surface morphology and photoelectric properties. (4th December 2017) - Sardar, Maryam; Chen, Jun; Ullah, Zaka; Jelani, Mohsan; Tabassum, Aasma; Cheng, Ju; Sun, Yuxiang; Lu, Jian
Abstract: We irradiate the single crystal boron-doped silicon (Si) with different number of laser pulses at constant fluence (7.5 J cm −2 ) in ambient air using Nd:YAG laser and examine its surface morphology and photoelectric properties in details. The results obtained from optical micrographs reveal the increase in heat affected zone (HAZ) and melted area of laser irradiated Si with increasing number of laser pulses. The SEM micrographs evidence the formation of various surface morphologies like laser induced periodic surface structures, crater, microcracks, clusters, cavities, pores, trapped bubbles, nucleation sites, micro-bumps, redeposited material and micro- and nano-particles on the surface of irradiated Si. The surface profilometry analysis informs that the depth of crater is increased with increase in number of incident laser pulses. The spectroscopic ellipsometry reveals that the multipulse irradiation of Si changes its optical properties (refractive index and extinction coefficient). The current–voltage ( I – V ) characteristic curves of laser irradiated Si show that although the multipulse laser irradiation produces considerable number of surface defects and damages, the electrical properties of Si are well sustained after the multipulse irradiation. The current findings suggest that the multipulse irradiation can be an effective way to tune the optical properties of Si for the fabrication of wide range of optoelectronic devices.